2014
DOI: 10.1590/1678-4499.0193
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de famílias e progênies de irmãos completos de cana-de-açúcar para atributos tecnológicos e de produção pelo método de REML/BLUP

Abstract: ResumoO objetivo deste trabalho foi avaliar as famílias e destacar as progênies superiores de cana-de-açúcar oriundas de 38 cruzamentos biparentais para os seguintes atributos: tonelada de colmos por hectare (TCH), toneladas de biomassa por hectare (TBIOH), brix (% caldo da cana), teor de fibra, pureza, pol e açúcar total recuperável (ATR). Os dados foram analisados via modelos mistos REML/BLUP, em que o REML (Máxima Verossimilhança Restrita) permitiu estimar parâmetros genéticos e BLUP (Melhor Predição Linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Notably, the selection of genotypes for the agronomic trait yielded significant gains through individual BLUP estimates. In previous studies on sugarcane, the mixed models methodology has been employed to select superior genotypes for biomass production (Lucius 2014;Oliveira et al 2008;Xavier et al 2014). These studies have shown that selecting genotypes with genotypic values above the experimental mean can lead to substantial gains in sugarcane yield per hectare.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the selection of genotypes for the agronomic trait yielded significant gains through individual BLUP estimates. In previous studies on sugarcane, the mixed models methodology has been employed to select superior genotypes for biomass production (Lucius 2014;Oliveira et al 2008;Xavier et al 2014). These studies have shown that selecting genotypes with genotypic values above the experimental mean can lead to substantial gains in sugarcane yield per hectare.…”
Section: Resultsmentioning
confidence: 99%
“…The PBS system that uses individualized sugarcane grinding wheels is a rapid multiplication technology that allows the reduction of the volume of vegetal material used in the planting, better control of vigor and high phytosanitary standard, promote sugarcane of excellent clonal standard. The fact of substantially reducing the volume of plant material needed for planting automatically results in a higher gain for the mills, since this material can be used for its production of alcohol or sugar, which will depend on the company's objective (Landell et al, 2013;Xavier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%